CAPITAL AND SURPLUS. - Littleton, A. C. (The Accounting Review, 1932)
Abstract A few year ago, particularly 1925 to 1930, certain tendencies in corporation finance were much under discussion among both accountants and lawyers. The accountants, by defining Earned Surplus, have indicated their approval of the subdivision of surplus into Earned Surplus and Capital Surplus and the lawyers, through Section 25 of the Uniform Statute, have shown that they favored a required subdivision of surplus which will produce separate accounts for paid-in surplus, revaluation surplus and surplus profits. Statutory provisions make it clear that accountants and lawyers still believe that the consideration given for shares of stock is an important indication of "capital," and that they still think of dividends as realized profits and not as capital returned. The most generally accepted use tends to associate the word surplus with profits or at least with the amount available for distribution. Therefore Paid-in Surplus will sound to most people like paid-in profit and Revaluation Surplus like revaluation profit and both will seem as if they should be distributable as dividends.